Analisis Literatur tentang Ilmu Pendidikan Islam dalam Perspektif Selamat Pohan - Ananda Pratiwi; Atika Khairunnisa; Ulfah Syahirah Putri; Rossa Azhara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This qualitative research article aims to analyze the basic concepts of Islamic education through the perspectives of two prominent thinkers: Dr. Selamat Pohan, S.Ag., MA. and Zailani, S.Ag., MA. This study specifically explores their views on the approaches, goals, and methodologies of Islamic education. Using content analysis and a comparative approach, this study identifies similarities and differences in the fundamental elements of Islamic education promoted by these two figures. The results indicate that both Selamat Pohan and Zailani view Islamic education as a holistic process encompassing moral strengthening, character formation, and the internalization of Islamic values in accordance with contemporary developments. Both emphasize the importance of an approach based on monotheism, goals aimed at the formation of a perfect human being, and an adaptive and contextual methodology for conveying Islamic values. This study contributes to the development of insights into contemporary Islamic education and enriches scientific discourse within the framework of spiritual and moral values-based education.